THE EFFECT OF APPLYING INTERACTIVE NOTATION SYSTEM FOR EFFECTIVE READING AND THINKING (INSERT) STRATEGY ON STUDENTS’ ACHIEVEMENT IN READING ANALYTICAL EXPOSITION TEXT - Poppy Priscilia Marbun and Tjut Ernidawati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study deals with the Effect of Applying Interactive Notation System forEffective Reading and Thinking (INSERT) Strategy on Students’ Achievement inReading Analytical Exposition Text. The objective of the study is to find outwhether Interactive Notation System for Effective Reading and Thinking(INSERT) Strategy significantly affects the students’ achievement in readinganalytical exposition text. It was an experimental research. The subject of thestudy was the students of eleventh (XI) grade students of SMA Negeri 1 TebingTinggi. The sample was divided into two groups. The Experimental group wastaught by applying Interactive Notation System for Effective Reading andThinking (INSERT) strategy, while the control group was taught by applyingQuestion Answer Relationship (QAR) strategy. Levels of reading comprehensionused in the reading test were literal, interpretative and critical reading. Thepercentages of each level were 35%, 45% and 20%.To obtain the reliability of thetest, the writer applied Kuder Richardson formula (KR-21). The result of thecalculation showed that the reliability of the test was 0.83, which means that thereliability of the test is very high. The data was analyzed by using t-test formula.The analysis showed that tobserved is exceeded than ttable (4.10 > 2.00) at the level ofsignificance of 0.05 with the degree of freedom (df) 58. The findings indicate thatusing Interactive Notation System for Effective Reading and Thinking (INSERT)strategy significantly affected the students’ reading analytical exposition text.